Effects of habitat use on food acquisition and food caching during a nonbreeding season in a winter-breeding, food-storing passerine. Issue 2 (2nd April 2020) - Nishida, Yuusuke; Takagi, Masaoki
ABSTRACT: Capsule: Wintering male Bull-headed Shrikes Lanius buchepalus preferred vegetable fields with perch sites to search for and detect terrestrial prey, and males occupying territories with large areas of vegetable fields acquired more prey and cached more food. Aims: To better understand effects of habitat use on food acquisition and food caching of the Bull-headed Shrike, we investigated relationships between habitat quality (measured through foraging-site selection and foraging success) and food caching during the non-breeding season. Methods: We monitored 66 territorial male shrikes during the non-breeding season from 2014 to 2016, and collected data on foraging-site selection, foraging success, and food caching. Results: Our field observations showed that male shrikes preferred to forage over vegetable fields and that males occupying territories incorporating large areas of that habitat were able to acquire more food items and store more food caches in their territories during the nonbreeding season. Conclusion: We suggest that for male Bull-headed Shrikes, a winter-breeding food-storing passerine, the quality of habitat in the nonbreeding season has the potential to affect their subsequent fitness.